Intra-African agricultural trade - Goundan, Anatole; Tadesse, Getaw (AKADEMIYA2063, 2021)
The Africa Agriculture Trade Monitor (AATM) was launched in 2018 as an annual report monitoring the continent’s progress in agricultural trade development. Chapter 3, as in the previous reports, reviews the state of intra-African agricultural trade, and provides an in-depth analysis of several agricultural products that are strategic for food security. Working from the hypothesis that total agricultural trade within Africa depends on the performance of trade in specific products, this chapter looks at how trade is affected by commodity-specific trade policies, including those related to food self-sufficiency, regulatory standards, and quality requirements.